The evaluation of both the expression and serum protein levels of Caspase‐3 gene in patients with different degrees of SARS‐CoV2 infection. Issue 3 (18th October 2021) - Yildiz Gulhan, Pinar; Eroz, Recep; Ataoglu, Ozlem; İnce, Nevin; Davran, Fatih; Öztürk, Cihadiye Elif; Gamsızkan, Zerrin; Balbay, Oner Abidin
Abstract: To evaluate the effects of Caspase‐3 ( CASP3 ) gene expression and serum levels on preventing severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. A total of 41 individuals (male: 21; female: 20) with SARS‐CoV‐2 infection were included in the current study. Hemograms were examined from patient blood samples, and CASP3 gene expression levels were detected. Also, human CASP3 levels were determined from the serum samples of patients. The mean age of patients was 56.220 ± 18.937 years. Significant differences were detected among all groups for CASP3  2 − ΔΔ C t ( p  = 0.014) and CASP3 concentration ( p  = 0.024). The relationship between CASP3 2 − ΔΔ C t levels and hemoglobin ( p  = 0.023), between CASP3 2 − ΔΔ C t levels and C‐reactive protein (CRP) ( p  = 0.001), between CASP3 2 − ΔΔ C t levels and ferritin ( p  = 0.003), between CASP3 2 − ΔΔ C t levels and lactate dehydrogenase ( p  =  0.001), and between CASP3 2 − ΔΔ C t levels and SpO2 ( p  = 0.006) were statistically significant. Also, the relationship between CASP3 concentration levels and SpO2 was statistically significant ( p  < 0.046). The CASP3 gene and/or its products have an important function to prevent injury caused by SARS‐CoV‐2 infection. They play crucial roles in maintaining cellular homeostasis and viability. Perhaps CASP3 levels may provide information about the severity of the disease. Highlights: Newly developed methods for pathogenesis; will guide the control of the epidemic in the future. The CASP3 gene and/or its products have an important function to prevent injury caused by SARS‐CoV‐2 infection. CASP3 gene can be a prognostic marker for the severity of COVID‐19 disease.